Keeping mum in clinical supervision: private thoughts and public judgements. Issue 2 (16th October 2018) - Scarff, Catherine E; Bearman, Margaret; Chiavaroli, Neville; Trumble, Steve
Abstract : Context: The seemingly obvious claim that people prefer to keep mum about undesirable messages – termed 'the MUM effect' – was initially reported in the psychology literature in the 1970s. More recently, it has been discussed in contexts including performance appraisals and the reporting of unsuccessful projects in workplace settings, but only sparsely in educational ones. We wished to review the published literature on the MUM effect in order to understand the implications for clinical assessment. Methods: We performed a narrative literature review on the MUM effect and clustered findings together into three themes: those that describe what MUM behaviours look like, those that explore potential reasons for the MUM effect and those that consider factors that can influence MUM behaviours. Results: This paper summarises the extensive literature on the MUM effect, including its manifestations and modifiers and discusses how the effect may be used to consider issues faced by many clinical supervisors faced with delivering 'negative' assessment messages to trainees. Discussion: We suggest, that as a pervasive phenomenon, the MUM effect can both help to explain the difficulties that some assessors face when delivering undesirable messages (including feedback or ratings) and offer new insights in how to deal with such issues. Abstract : This paper provides a narrative review of the the tendency to not disclose concerns during clinical supervision and offers insight into how knowledge of this phenomenon might inform assessment practices.